2019
DOI: 10.1016/j.cell.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Melanoma Response to Immunotherapy Reveals Mitochondrial Dependence

Abstract: Immunotherapy has revolutionized cancer treatment, yet most patients do not respond. Here, we investigated mechanisms of response by profiling the proteome of clinical samples from advanced stage melanoma patients undergoing either tumor infiltrating lymphocyte (TIL)-based or anti-programmed death 1 (PD1) immunotherapy. Using high-resolution mass spectrometry, we quantified over 10,300 proteins in total and $4,500 proteins across most samples in each dataset. Statistical analyses revealed higher oxidative phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(197 citation statements)
references
References 85 publications
(99 reference statements)
6
190
0
1
Order By: Relevance
“…Recently, high tumor antigen and metabolic protein expression levels have been shown to be predictive of checkpoint inhibitor response in melanoma, suggesting that CDK4/6i could be used in conjunction with checkpoint blockade or TIL-based therapies to increase tumor immunogenicity. 52 As an alternate therapeutic strategy, peptide antigens whose surface 17 expression was selectively increased by CDK4/6i could be utilized for targeted immunotherapy, either alone or in combination.…”
Section: Repertoire Changes Induced By Ifn-g Stimulation Are Distinctmentioning
confidence: 99%
“…Recently, high tumor antigen and metabolic protein expression levels have been shown to be predictive of checkpoint inhibitor response in melanoma, suggesting that CDK4/6i could be used in conjunction with checkpoint blockade or TIL-based therapies to increase tumor immunogenicity. 52 As an alternate therapeutic strategy, peptide antigens whose surface 17 expression was selectively increased by CDK4/6i could be utilized for targeted immunotherapy, either alone or in combination.…”
Section: Repertoire Changes Induced By Ifn-g Stimulation Are Distinctmentioning
confidence: 99%
“…119,172 Accordingly, good response to immunotherapy was associated with enriched mitochondrial metabolism in melanoma patients. 173 Surprisingly, the opposite finding was reported regarding PD-1 blockade in a melanoma study showing that tumor oxygen consumption was associated with T cell exhaustion and progression under checkpoint blockade. 174 Nevertheless, the efficacy of checkpoint blockade was improved by LDH suppression in murine tumors.…”
Section: Targ E Ting the Warburg Effec T For Tumor Ther Apy And Immmentioning
confidence: 92%
“…Good response to checkpoint blockade a 84,119,173,175 Renal cell carcinoma Lower T cell infiltration, inferior response to checkpoint blockade 24,172 Colon cancer Lower CD8 T cell infiltration 25 Head and neck squamous cell carcinoma Lower CD8 T cell infiltration 26 Lung squamous cell carcinoma Lower CD8 T cell infiltration 26 Lung adenocarcinoma Lower T cell infiltration 55 Lung carcinoma Impaired anti-tumor T cell response 17 Prostate cancer Reduced anti-tumoral Th1 cells 115 a A contradictory finding by Najjar et al 174 who found high tumor OXPHOS as a barrier to checkpoint blockade.…”
Section: Melanoma Decreased T Cell Activity Inferior Response To Chementioning
confidence: 99%
“…The accuracy and sensitivity of these machines has propelled HR/MS to be applied in fields such as proteomics and metabolomics. [ 128–130 ] HR/MS can utilize both the bottom‐up approach [ 131 ] as well as sequence intact proteins (top‐down approach). [ 132 ] Both these approaches complement each other and allow deeper understanding of protein expression profiles, leading to better diagnosis and classification of diseases.…”
Section: Mass Spectrometrymentioning
confidence: 99%